Natural incidence of aflatoxins, ochratoxin A and zearalenone in chicken meat and eggs - Iqbal, Shahzad Zafar; Nisar, Sonia; Asi, Muhammad Rafique; Selamat, Jinap (Elsevier, 2014)
Aflatoxins (AFs), ochratoxin A (OTA) and zearalenone (ZEN) were analyzed in 115 chicken meat and 80 eggs samples, collected from central areas of Punjab, Pakistan. The study was carried out using reverse phase HPLC, equipped with fluorescence detector. The results revealed that 35% samples of chicken and 28% samples of eggs were found contaminated with AFs, and maximum level of AFB1 and total AFs was found in the liver part of chicken (layer) 7.86 and 8.01 μg/kg, respectively. Furthermore, 41% samples of chicken and 35% sample of eggs were found contaminated with OTA and maximum level 4.70 μg/kg was found in the liver part of chicken meat. However, 52% samples of meat and 32% samples of eggs were found contaminated with ZEN and maximum level 5.10 μg/kg was found in the liver part of chicken meat. The occurrence and incidence of AFs, OTA and ZEN in chicken meat and eggs are alarming and it may produce health hazards and urged the need of continuous monitoring for these toxins in chicken meat and eggs.